2020
DOI: 10.1016/j.heliyon.2020.e04447
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chlorella sorokiniana and Chlorella vulgaris fatty acid components under a wide range of light intensity and growth temperature for their use as biological resources

Abstract: This study aims to characterize the potential of three strains of microalgal species ( Chlorella sorokiniana KNUA114 and KNUA122; C. vulgaris KNUA104) for use as feedstock, based on their fatty acid compositions. Each strain was molecularly identified using four marker genes ( ITS , SSU , rbcL , and tufA ) and phylogenetically characterized. C. sorokiniana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 81 publications
0
23
0
1
Order By: Relevance
“…Previous studies have determined the optimal growth temperature conditions for Chlorella vulgaris and Chlorella sorokiniana (Yun et al, 2020). Furthermore, it was found that an organic carbon source in a heterotrophic condition could be utilized by Chlorella (Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have determined the optimal growth temperature conditions for Chlorella vulgaris and Chlorella sorokiniana (Yun et al, 2020). Furthermore, it was found that an organic carbon source in a heterotrophic condition could be utilized by Chlorella (Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…1a and b with some key observed features of UJEAS4 (Fig. 1a) as having spherical shaped cells with no flagella and the average sizes varied between 3 and 4 and 5 and 6 µm, which is a common feature of the genus Chlorella [4,39,40].…”
Section: Isolation and Identification Of Microalgal Strainsmentioning
confidence: 93%
“…Saturated fatty acids (SFAs) have been described in numerous studies as biological tools for biodiesel production and microalgae are rich sources of these compounds [4]. The percentage of SFA content for C. sorokiniana and T. reginae corresponds to 35.73 ± 1.13% and 29.79 ± 1.06%, respectively.…”
Section: Biochemical Composition Elemental Composition and Fatty Acid Methyl Ester Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Three flocculation bacterial strains (M. jejuensis KCTC 32230, C. flocculans KCTC 62943, and E. coli, dh5α) and the microalgal strain C. sorokiniana KNUA114 were prepared. C. sorokiniana KNUA114 was isolated from Okcheon Stream in Ulleung, Korea (Okcheon Stream, Ulleungeup, Ulleung-gun, Gyeongsangbuk-do; 37 Yun et al, 2020). The bacterial and algal strains were maintained at 30 • C on R2A agar plates composed of the following: proteose peptone, 0.5 g/L; casamino acid, 0.5 g/L; yeast extract, 0.5 g/L; dextrose, 0.5 g/L; soluble starch, 0.5 g/L; sodium pyruvate, 0.3 g/L; K 2 HPO 4 , 0.3 g/L; and MgSO 4 •7H 2 O, 0.05 g/L.…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%